2018
DOI: 10.1089/ten.tea.2018.0065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platelet-Rich Plasma on Chondrogenic Differentiation of Adipose- and Bone Marrow-Derived Mesenchymal Stem Cells

Abstract: Post-traumatic and focal cartilage defects of the knee affect over 3 million Americans annually. Autologous cell-based cartilage repair, for example, autologous chondrocyte implantation, is limited by the need for ex vivo chondrocyte expansion and donor site morbidity. Mesenchymal stem cells (MSCs), owing to their relative ease of isolation, higher replication activity, and chondrogenic potential, represent an alternative reparative cell type. Platelet-rich plasma (PRP) is an autologous, growth factor-rich bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 55 publications
4
48
0
Order By: Relevance
“…The fastest stress relaxation of hydrogels with First, we demonstrated that it was necessary to use a higher concentration of hBM-MSCs for obtaining their chondrogenic differentiation. In fact, by only using 10 6 hBM-MSCs, it was possible to reach a cell condensation necessary to promote their chondrogenic differentiation, as also reported by other studies (Agrawal et al, 2018;Liou, Rothrauff, Alexander, & Tuan, 2018;Occhetta et al, 2018). Moreover, we also evidenced that in static condition, a longer time point (Day 48) was necessary to obtain a scaffold completely filled both outside and inside.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The fastest stress relaxation of hydrogels with First, we demonstrated that it was necessary to use a higher concentration of hBM-MSCs for obtaining their chondrogenic differentiation. In fact, by only using 10 6 hBM-MSCs, it was possible to reach a cell condensation necessary to promote their chondrogenic differentiation, as also reported by other studies (Agrawal et al, 2018;Liou, Rothrauff, Alexander, & Tuan, 2018;Occhetta et al, 2018). Moreover, we also evidenced that in static condition, a longer time point (Day 48) was necessary to obtain a scaffold completely filled both outside and inside.…”
Section: Discussionsupporting
confidence: 84%
“…Our data evidenced that HPL chronically used during hBM‐MSCs chondrogenic differentiation decreased typical chondrogenic, hypertrophic, and fibrotic makers during time in culture. Other reports (Liou et al, ; Moreira Teixeira et al, ) have confirmed that HPL counteracted the positive effects on hBM‐MSC chondrogenesis by reducing collagen type 2 and aggrecan. Recently, Liou et al () carried out an in‐depth evaluation on the effects of both different HPL concentration and time of exposure on hBM‐MSCs chondrogenic differentiation and showed that chondrogenesis was inhibited with increasing HPL concentration and duration of exposure.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…[26] As already stated, the therapeutic properties of PRP are based on the presence of PDGF, TGF-β, VEGF, IGF-I, PF4, EGF, HGF, and SDF-1α stored in the platelet a-granules. [407] 6. The standardization of procedures for the use of PRP and selection criteria for subjects who will maximally benefit from the procedure will hopefully minimize this biological spread.…”
Section: Prp As a Therapeutic Treatment For Mild To Moderate Knee Oa:mentioning
confidence: 99%
“…(39,40) Consequently, some successful outcomes are attributed to factors transiently produced by the donor cells that influence a successful host reparative response. (47) However, the biological action of PRP, eg, in regulating differentiation of multipotent MSCs, (48) remains unclear. If these factors could be identified, they could be used directly without the need for supplying the producing cells.…”
Section: Pluripotent Stem Cells (Embryonic Stem Cells) and Induced Plmentioning
confidence: 99%